The anti-plaque effect of high concentration sodium bicarbonate dentifrice on plaque formation and gingival inflammation, irrespective to individual polishing technique and plaque quality - Siren Abrahamsen; Odd Carsten Koldsland; Hans R. Preus (BMC, 2023)
Abstract Aim To assess the anti-plaque effect of a high concentration sodium bicarbonate dentifrice on plaque formation, and gingivitis, as compared to a control toothpaste, irrespective of individual brushing technique and plaque quality. Methods The experimental gingivitis model, with a split-mouth design was used to assess the anti-plaque effect of a high concentration sodium bicarbonate dentifrice on plaque formation. By producing individual fitted trays, the toothpaste was applied in the test quadrant and a control dentifrice in the contralateral. The participants used the individual fitted trays for 1 min every morning and evening, for 21 days. In this period, the participants was only allowed to brush the teeth in the opposite jaw, as usual. Twenty healthy individuals successfully completed the study. Results At 21 days, there was no statistically significant difference between test quadrant and control quadrant with regard to plaque indices, gingival index and number of bleeding sites. Conclusion This study demonstrated that the high concentration sodium bicarbonate dentifrice used did not produce statistically significant anti-plaque effect compared to the control dentifrice, in terms of Plaque- and Gingival Indices, number of bleeding sites or by Quigely and Hein, the Turesky modification Plaque Index, irrespective of brushing technique and individual plaque quality. Trial registration Regional Committee for Medical Research and Ethics, South-East Norway in 2021 (REK.2021/370116). Clinical Trial Registration: NCT05441371 (First registered 09/06/2022, First posted 01/07/2022) ( http://www.clinicaltrials.gov ). (Retrospectively registered).